Level of scientific argumentation ability of students in biology learning - Lidya Hasmaningsih; Karnan Karnan; Baiq Sri Handayani (Jurnal Pijar Mipa, 2022)
Scientific argumentation is one of the skills needed in the 21st century. The purpose of this study was to analyze the level of scientific argumentation ability of students in class XI biology learning using plant tissue material at SMAN 1 Labuhan Haji. The research method used is descriptive qualitative with research instruments in the form of scientific argumentation ability tests, questionnaires, and interviews. The population in this study amounted to 133 people. The sample was selected using the census technique so that it used a saturated sample or all members of the population, namely class XI MIPA 1, XI MIPA 2, XI MIPA 3, and XI MIPA 4. The results showed that the student's written and oral scientific argumentation skills were still low and needed to be empowered again. Students' written scientific argumentation ability is at level 2 with a percentage of 74.9%, and oral scientific argumentation is at level 2 with a percentage of 73%.